Preparation method of granite stone powder modified high-performance concrete

By physical modification and chemical modification of granite rock powder, combined with the synergistic effect of epoxy resin and wood fibers, the problems of reduced fluidity, low strength and poor durability in concrete are solved, and the preparation of high-performance concrete is achieved.

CN119797846AActive Publication Date: 2025-04-11POLY CHANGDA ENGINEERING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510016482.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

When granite stone powder is used as a blend in concrete, it leads to reduced concrete fluidity, low strength and poor durability.

Method used

Through physical modification and carbonation chemical modification, the specific surface area and effective contact area of ​​granite stone powder are increased, its filling effect in concrete is improved, and the mechanical properties and durability of concrete are improved through synergistic effects with epoxy resin and wood fibers.

Benefits of technology

It improves the flowability and mechanical properties of concrete, enhances its durability, and solves the problems of reduced concrete flowability and low strength caused by granite stone powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of concrete preparation, in particular to a preparation method of granite stone powder modified high-performance concrete, which comprises the following steps: adding dry granite stone powder of less than or equal to 40 meshes into epoxy resin emulsion, and mixing and stirring to obtain modified epoxy resin; pretreating the dried wood fibers by using an alkaline solution, cleaning and drying for later use; dry granite powder with the particle size smaller than or equal to 200 meshes is mixed with polyester resin, ethyl potassium peroxide and a cobalt drier solution, the pretreated wood fibers are modified, and modified wood fibers are obtained; introducing carbon dioxide and nitrogen into the ground granite stone powder in an alkaline solution to carry out carbonation modification treatment; uniformly mixing the modified wood fiber and the treated granite stone powder with cement, fly ash, aggregate, water and an additive, adding the modified epoxy resin, and uniformly stirring to prepare concrete; and adding redispersible latex powder according to the fluidity of the concrete, and stirring again to obtain the granite stone powder modified high-performance concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete preparation, and in particular to a method for preparing high-performance concrete modified by granite powder. Background Art

[0002] A large amount of stone powder will be produced during the production of artificial sand. If the stone powder is not used properly, it will cause environmental pollution and waste resources. The mineral composition of artificial sand and stone powder is the same as that of the parent rock. It can replace cement or traditional mineral admixtures such as fly ash, slag powder, etc. as a mineral admixture for concrete preparation.

[0003] According to the mineral composition, machine-made sand and gravel powder can be roughly divided into: calcium rock base stone powder and siliceous rock base stone powder. Generally, calcium rock base stone powder is more compatible with water reducers than siliceous rock base stone powder. This is mainly because calcium stone powder is mostly in an island structure with low water absorption, while siliceous stone powder is mostly in a layered hydrophilic structure with high water absorption, resulting in an increase in the water demand ratio of stone powder. If the stone powder content is too high, the concrete mixture will become viscous and have low fluidity, which will in turn affect the strength and durability of hardened concrete. The main component of granite is SiO 2 , which belongs to siliceous rock, the mica particles in the stone powder are flake-shaped, with low strength, easy to dislocate along the joint surface, and the internal interlayer structure is complex and special, with strong adsorption, which leads to the increase of water demand of granite stone powder. And granite is a low-activity stone powder. If it is directly used as a mineral admixture to prepare concrete, it will be detrimental to the strength of concrete.

[0004] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0005] The technical problem to be solved by the present invention is: to provide a method for preparing high-performance concrete modified with granite powder, to increase the effective contact area of ​​the granite powder and the specific surface area through physical modification, and to improve the filling effect thereof; to change the surface morphology of the granite powder through carbonation chemical modification, to make it rougher and require more water to cover the surface, which will lead to reduced fluidity, but improved mechanical properties due to improved interface; and to use the processed granite powder as an admixture to help improve mechanical properties and durability.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing high-performance concrete modified by granite powder comprises the following steps:

[0008] S01: Add dry granite powder of ≤40 mesh into epoxy resin emulsion in proportion, mix and stir for 15 to 20 minutes to obtain modified epoxy resin;

[0009] Preferably, step S01 specifically includes: screening the granite powder through a 40-mesh (425 micron) square hole sieve, drying the screened granite powder at 100-120°C for 10-15 hours, strictly controlling the water content in the granite powder to prevent the appearance of bubbles; then weighing the dried granite powder in a dry environment, adding it to the epoxy resin emulsion according to the ratio, mixing and stirring for 15-20 minutes under dry conditions to reduce the influence of tension, and preparing the modified epoxy resin. Smaller particles (such as 425 microns) can be more evenly dispersed in the epoxy resin, reducing particle accumulation or sedimentation, which helps to prepare a more uniform modified epoxy resin and improve its application effect in concrete.

[0010] Granite powder, as an inorganic filler, plays a reinforcing role in epoxy resin. Its tiny particles can improve the hardness, rigidity and compressive strength of the resin by mixing with epoxy resin emulsion. In addition, granite powder can also improve the wear resistance, impact resistance and heat resistance of the resin, and can enhance the bonding performance of epoxy resin in concrete, especially on cement matrix or other filling materials, and improve the effect of modified epoxy resin as an interface material in concrete.

[0011] S02: pre-treating the dried wood fiber with an alkaline solution, then washing and drying it for later use;

[0012] Preferably, in step S02, the dried wood fiber is added to a 5% NaOH solution, and the dried wood fiber is immersed in the alkaline solution at room temperature for 2 to 2.5 hours; the immersed wood fiber is taken out, and is thoroughly rinsed with distilled water to remove the NaOH adhering to the surface of the wood fiber, and the wood fiber is placed in a constant temperature box and dried at 100±5°C for 20 to 30 hours to stabilize the fiber structure and ensure that it does not change during subsequent processing.

[0013] Wood fiber is mainly composed of cellulose, hemicellulose and lignin, among which cellulose is the main structural component. The pretreatment of wood fiber with alkaline solution (NaOH) mainly acts through alkaline hydrolysis reaction, involving the removal of lignin, hydrolysis of hemicellulose, ring opening and partial degradation of cellulose. After alkaline treatment, NaOH destroys the non-polar structure of wood fiber, making the fiber surface rich in polar groups (such as hydroxyl, carboxyl, etc.). These polar groups can form hydrogen bonds or other interactions with other polar substances (such as water, resin, etc.), enhancing its adhesion with modified materials such as polyester resin and granite powder. Alkaline treatment will also cause a certain degree of coarsening of the surface of wood fiber, increase the specific surface area of ​​the fiber, and help improve the interface bonding between wood fiber and other materials, thereby improving the modification effect.

[0014] S03: Mixing dried granite powder with a mesh size of ≤200 with polyester resin, potassium peroxide acetone, and cobalt drier solution in proportion, and modifying the wood fiber pretreated in step S02 to obtain modified wood fiber;

[0015] Preferably, step S03 specifically includes:

[0016] The granite powder is sieved through a 200-mesh (75-micron) square hole sieve, and the sieved granite powder is dried at 100-120° C. for 10-15 hours; a polyester resin, methyl ethyl ketone peroxide, and a cobalt drier solution are prepared, and the dried granite powder is mixed in a ratio of 100:1-1.5:1-1.5:10-15; the mixture is stirred at a low speed for 10-20 minutes to ensure uniform mixing; the wood fiber is soaked in the mixed solution for 25-35 minutes, and after being taken out, it is spread on a smooth surface, and a pressing plate is used to apply a pressure of 20 kg; the mixture is cured at room temperature for 24 hours, and then further cured at 60-85° C. for 2 hours.

[0017] Wood fiber itself has components such as cellulose, hemicellulose and lignin. Through the immersion of polyester resin, the active groups in the resin (such as hydroxyl, carbonyl, etc.) can chemically bond with the cellulose, hemicellulose and other components in the wood fiber, thereby enhancing the stability and bonding properties of the wood fiber. The presence of polyester resin can fill the gaps in the wood fiber and enhance its structural strength after curing. Due to the synergistic effect of potassium peroxide acetone and cobalt drier, the resin layer on the surface of the wood fiber can be quickly cured, providing stronger surface adhesion and better mechanical properties. The granite powder is bonded with polyester resin and cured under pressure, and is well combined with the surface of the granite powder, which improves the tensile, bending and impact resistance of the wood fiber. After modification, the fibers are more dispersed and laid flat on the surface, and finally cured into long flakes. After the final addition, stir together to ensure dispersion.

[0018] S04: introducing carbon dioxide and nitrogen into an alkaline solution to perform carbonation modification treatment on the ground granite powder;

[0019] Preferably, step S04 includes physical modification and chemical modification of granite powder.

[0020] The physical modification is as follows: drying the granite powder in an oven at 100-120°C, mixing it evenly with a grinding aid after cooling, and then grinding it in a ball mill; wherein the grinding aid is prepared from triethanolamine and ethylene glycol in a mass ratio of 1:1, and the mass of the grinding aid is 0.2% of the mass of the granite powder.

[0021] The chemical modification is as follows: a 0.1 mol / L NaOH solution is prepared in a glass container (or other non-reactive container), ground granite powder is added to the solution, carbon dioxide and nitrogen are introduced into the NaOH solution, the gas flow rates are 7-9 L / h and 3-5 L / h, respectively, the ventilation time is 60-80 minutes, the reaction is carried out at 25°C±5°C, after the reaction is completed, the mixture is separated into solid and liquid, and the separated solid is dried at 105°C to constant weight.

[0022] The granite powder after grinding has a smaller particle size and a higher specific surface area, which will enhance the filling effect of the granite powder, reduce the porosity, optimize the pore structure, and enhance the nucleation effect after subsequent chemical modification. Granite powder contains a small amount of CaO. After chemical modification, this part of CaO can be fully utilized to modify the surface of the granite powder. 2 In the granite powder introduced into the water environment, part of the CaO is converted into CaCO 3 Due to its low solubility, it precipitates and adsorbs on the surface of granite powder. This not only increases the roughness of the granite powder surface and improves its bonding ability in cement, but also plays a nucleation role similar to limestone powder due to the calcite structure on the surface, thus improving the hydration degree of cement.

[0023] S05: uniformly mixing the modified wood fiber obtained in step S03 and the granite powder treated in step S04 with cement, fly ash, aggregate, water and additives, and then adding the modified epoxy resin obtained in step S01 and mixing them uniformly to prepare concrete;

[0024] Preferably, in step S05, the aggregate includes ore and machine-made sand, the additive is a water reducer, and the mass ratio of modified epoxy resin, modified wood fiber, treated granite powder, cement, fly ash, ore, machine-made sand, water and water reducer is 28-31:6-9:55-65:230-250:55-65:980-1005:835-860:165-175:2.5-3.6.

[0025] Preferably, in step S05, machine-made sand and modified wood fiber are placed in a forced concrete mixer in a mass ratio of 1:10, and then the treated granite powder, cement, fly ash, remaining aggregate, water and water reducer are added and stirred for 2 minutes, and finally modified epoxy resin is added and wet mixed for 2 minutes to obtain high-performance concrete modified with granite powder.

[0026] S06: Detect the fluidity of the obtained concrete, add 0-1% of redispersible latex powder as a cementitious material and stir again to obtain high-performance concrete modified by granite powder.

[0027] The amount of redispersible latex powder added is determined according to the fluidity of the obtained concrete. If the fluidity of the obtained concrete is too low, 1% (2.8-3.1 parts) of redispersible latex powder can be added to the cementitious material and stirred again for 2 minutes. If the fluidity is still too low, repeat this operation, but pay attention that the total amount of redispersible latex powder does not exceed 3% of the cement. For every 12mm the slump of the concrete is lower than the design value, 1% (2.8-3.1 parts) of redispersible latex powder can be added for trial mixing. The introduction of redispersible latex powder will bring a large number of bubbles and reduce the mechanical properties. In order to eliminate this effect, a defoamer is introduced to improve the mechanical properties of concrete. For every 1 part of redispersible latex powder added, 0.01 part of defoamer should be added. Taking GP330 defoamer as an example, the chemical formula is C 31 H 39 N 4 O 10 .

[0028] The beneficial effects of the present invention are:

[0029] In addition to modifying the granite powder itself, the present invention utilizes the good synergy between granite powder, epoxy resin and wood fiber to prepare modified epoxy resin and modified wood fiber. Granite powder modified wood fiber helps to reduce the water absorption rate of wood fiber, improve thermal stability, improve tensile strength, bending resistance and impact resistance, and help to better play in concrete. Granite powder modified epoxy resin increases its water absorption rate after modifying epoxy resin, making it a highly water-absorbent material with excellent water absorption and desorption properties. When the relative humidity inside the concrete decreases, the water-absorbent material can release the absorbed water, which supplements the water consumption required for hydration, ensures the continuous formation of hydration products, fills the pores of concrete, reduces the adverse effects caused by the formation of microcracks and shrinkage and self-shrinkage, and achieves the effect of internal maintenance. Prepare modified epoxy resin as an admixture and modified wood fiber as an additional fiber to improve the strength and durability of concrete.

[0030] After the concrete is trial-mixed, the combination of redispersible latex powder and defoamer is used to adjust the concrete fluidity to meet the use requirements. Various properties of concrete are improved by means of chemical modification, physical grinding, particle stacking and filling, and adding admixtures, so as to solve the problems that granite powder as an admixture reduces the concrete fluidity, low hydration activity reduces the hydration product and reduces the strength, and poor particle size distribution increases the porosity and reduces the durability, and prepares high-performance granite powder concrete with good performance. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0033] Materials and commercial sources:

[0034]

[0035]

[0036] Example 1

[0037] A method for preparing high-performance concrete modified by granite powder comprises the following steps:

[0038] S01: sieving the granite powder through a 40-mesh (425 micron) square hole sieve, drying the sieved granite powder at 120° C. for 12 hours, strictly controlling the water content in the granite powder to prevent the appearance of bubbles; then weighing the dried granite powder in a dry environment, adding it to the epoxy resin emulsion according to the ratio, mixing and stirring for 15 minutes under dry conditions to reduce the influence of tension, and preparing the modified epoxy resin;

[0039] S02: Add the dried wood fiber to a 5% NaOH solution, and immerse the dried wood fiber in the alkaline solution at room temperature for 2 hours; take out the immersed wood fiber, rinse it thoroughly with distilled water to remove the NaOH adhering to the surface of the wood fiber, and put the wood fiber in a constant temperature box and dry it at 100±5℃ for 24 hours;

[0040] S03: Screen the granite powder through a 200-mesh (75-micron) square hole sieve, and dry the screened granite powder at 120°C for 12 hours; prepare polyester resin, methyl ethyl ketone peroxide, and cobalt drier solution, and mix them with the dried granite powder in a ratio of 100:1:1:10; stir at a low speed for 15 minutes to ensure uniform mixing; soak the wood fiber in the above mixed solution for 30 minutes, take it out and lay it flat on a smooth surface, use a pressing plate and apply a pressure of 20kg; cure it at room temperature for 24 hours, and further cure it at 70°C for 2 hours;

[0041] S04: Dry the granite powder in an oven at 105°C, mix it evenly with a grinding aid after cooling, and then grind it in a ball mill; wherein the grinding aid is prepared from triethanolamine and ethylene glycol in a mass ratio of 1:1, and the mass of the grinding aid is 0.2% of the mass of the granite powder; prepare a 0.1 mol / L NaOH solution in a glass container (or other non-reactive container), add the ground granite powder to the solution, pass carbon dioxide and nitrogen into the NaOH solution, the gas flow rates are 8L / h and 4L / h respectively, the ventilation time is 60 minutes, the reaction is carried out at 23°C, and after the reaction is completed, the mixture is separated into solid and liquid, and the separated solid is dried at 105°C to constant weight;

[0042] S05: Put machine-made sand and modified wood fiber in a mass ratio of 1:10 into a forced concrete mixer, then add treated granite powder, cement, fly ash, remaining aggregate, water and water reducer and continue stirring for 2 minutes, finally add modified epoxy resin and wet mix for 2 minutes to obtain high-performance concrete modified with granite powder; wherein the mass ratio of modified epoxy resin, modified wood fiber, treated granite powder, cement, fly ash, crushed stone, machine-made sand, water and water reducer is 30:9:60:240:60:998:849:170:2.6.

[0043] S06: The fluidity of the obtained concrete is tested, and 3% of redispersible latex powder and 0.003% of defoaming agent as a cementitious material are added and stirred again to obtain high-performance concrete modified by granite powder.

[0044] Example 2: The difference between this example and Example 1 is that in step S03, the mixing ratio of polyester resin, methyl ethyl ketone peroxide, cobalt drier solution, and granite powder after drying is changed to 100:1.5:1.5:15. Other details will not be repeated.

[0045] Example 3: The difference between this example and Example 1 is that in step S06, the amount of redispersible latex powder added is changed to 5%, and the amount of defoaming agent added is changed to 0.005%. Other details will not be described in detail.

[0046] Comparative Example 1:

[0047] The difference between this embodiment and embodiment 1 is that in step S05, the mass ratio of modified epoxy resin, modified wood fiber, treated granite powder, cement, fly ash, ore, machine-made sand, water and water reducing agent is 0:0:60:240:60:998:849:170:2.6. Other details are not repeated here.

[0048] Comparative Example 2:

[0049] The difference between this embodiment and embodiment 1 is that in step S05, the mass ratio of modified epoxy resin, modified wood fiber, treated granite powder, cement, fly ash, crushed stone, machine-made sand, water and water reducing agent is 9:9:0:240:60:998:849:170:2.6. Other details are not repeated here.

[0050] Comparative Example 3:

[0051] The difference between this embodiment and embodiment 1 is that in step S05, the mass ratio of modified epoxy resin, modified wood fiber, treated granite powder, cement, fly ash, crushed stone, machine-made sand, water and water reducing agent is 9:9:0:240:60:998:849:170:2.6. No redispersible latex powder is added to obtain high-performance concrete modified with granite powder.

[0052] Table 2. Performance test data

[0053]

[0054] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing high-performance concrete modified by granite powder, characterized in that: The steps are as follows: S01: Add dry granite powder of ≤40 mesh into epoxy resin emulsion in proportion, mix and stir for 15-20 minutes to obtain modified epoxy resin; S02: pre-treating the dried wood fiber with an alkaline solution, then washing and drying it for later use; S03: Mixing dried granite powder with a mesh size of ≤200 with polyester resin, potassium peroxide acetone, and cobalt drier solution in proportion, and modifying the wood fiber pretreated in step S02 to obtain modified wood fiber; S04: introducing carbon dioxide and nitrogen into an alkaline solution to perform carbonation modification treatment on the ground granite powder; S05: uniformly mixing the modified wood fiber obtained in step S03 and the granite powder treated in step S04 with cement, fly ash, aggregate, water and additives, and then adding the modified epoxy resin obtained in step S01 and mixing them uniformly to prepare concrete; S06: Detect the fluidity of the obtained concrete, add 0-1% redispersible latex powder as a cementitious material and stir again to obtain high-performance concrete modified by granite powder.

2. The method for preparing high-performance concrete modified by granite powder according to claim 1, characterized in that: Step S01 specifically includes: screening granite powder through a 40-mesh sieve, drying the screened granite powder at 100-120° C. for 10-15 hours, weighing the dried granite powder and adding it to the epoxy resin emulsion according to the ratio, mixing and stirring under dry conditions for 15-20 minutes to obtain the modified epoxy resin.

3. The method for preparing high-performance concrete modified by granite powder according to claim 1, characterized in that: Step S02 specifically includes: adding the dried wood fiber to a 5% NaOH solution and soaking it at room temperature for 2 to 2.5 hours; taking out the wood fiber, thoroughly rinsing it with distilled water, and then putting it in an oven to dry it at 100±5°C for 20 to 30 hours.

4. The method for preparing high-performance concrete modified by granite powder according to claim 1, characterized in that: Step S03 specifically includes: screening the granite powder through a 200-mesh sieve, and drying the screened granite powder at 100-120°C for 10-15 hours; preparing polyester resin, methyl ethyl ketone peroxide, and cobalt drier solution, and mixing them with the dried granite powder in proportion; stirring at a low speed for 10-20 minutes to ensure uniform mixing; soaking the wood fiber in the above mixed solution for 25-35 minutes, taking it out and flattening it on a smooth surface, using a pressing plate and applying a pressure of 20kg; curing at room temperature for 24 hours, and further curing at 60-85°C for 2 hours.

5. The method for preparing high-performance concrete modified by granite powder according to claim 4, characterized in that: In step S03, the mass ratio of the polyester resin, methyl ethyl ketone peroxide, cobalt drier solution and the dried granite powder is 100: 1-1.5: 1-1.5: 10-15.

6. The method for preparing high-performance concrete modified by granite powder according to claim 1, characterized in that: Step S04 specifically includes: drying the granite powder in an oven at 100-120°C, mixing it evenly with a grinding aid after cooling, and then grinding it in a ball mill; preparing a 0.1 mol / L NaOH solution in a glass container, adding the ground granite powder to the solution, passing carbon dioxide and nitrogen into the NaOH solution at gas flow rates of 7-9 L / h and 3-5 L / h, respectively, for 60-80 minutes, reacting at 20-30°C, separating the mixture into solid and liquid after the reaction, and drying the separated solid at 100-120°C to constant weight.

7. The method for preparing high-performance concrete modified by granite powder according to claim 6, characterized in that: In step S04, the grinding aid is prepared from triethanolamine and ethylene glycol in a mass ratio of 1:1, and the mass of the grinding aid is 0.2% of the mass of the granite powder.

8. The method for preparing high-performance concrete modified by granite powder according to claim 1, characterized in that: In step S05, the aggregate includes ore and machine-made sand, the additive is a water reducer, and the mass ratio of modified epoxy resin, modified wood fiber, treated granite powder, cement, fly ash, ore, machine-made sand, water and water reducer is 28~31:6~9:55~65:230~250:55~65:980~1005:835~860:165~175:2.5~3.

6.

9. The method for preparing high-performance concrete modified by granite powder according to claim 8, characterized in that: Step S05 specifically includes: putting machine-made sand and modified wood fiber into a mixer in a mass ratio of 1:10, then adding treated granite powder, cement, fly ash, remaining aggregate, water and water reducing agent and continuing to stir, and finally adding modified epoxy resin and wet mixing to obtain high-performance concrete modified by granite powder.

10. The method for preparing high-performance concrete modified by granite powder according to claim 1, characterized in that: In step S06, the total amount of redispersible latex powder does not exceed 3% of the cement, and 0.01 part of defoaming agent is added for every 1 part of redispersible latex powder added.

Citation Information

Patent Citations

  • Super high performance concrete prepared by wet granite stone powder and preparation method thereof

    CN107892527A

  • Self-luminous water permeable brick and preparation method thereof

    CN109678404A

  • Concrete based on granite stone powder and preparation method thereof

    CN115477529A

  • Concrete resistant to chlorine salt dry-wet cycle erosion and recycling method thereof

    CN117125933A

  • Production of architectural material

    JP1994122115A